O-069 Does dual stimulation with continuous FSH administration increase the total number of metaphase II oocytes in poor responders?. (30th June 2022) - Boudry, L; Racca, A; Mackens, S; Tournaye, H; De Vos, M; Drakopoulos, P; Blockeel, C
Abstract: Study question: Is there an increase in the total number of metaphase II (MII) oocytes between a conventional ovarian stimulation and a dual uninterrupted stimulation? Summary answer: Dual stimulation with continuous follicle stimulating hormone (FSH) administration is not superior to conventional stimulation in terms of number of MII oocytes. What is known already: In the last decade, the concept of multiple follicular waves during one menstrual cycle has gained a lot of interest. Translated into clinical practice, combining two stimulations in the same ovarian cycle has appeared beneficial with regard to the number of retrieved oocytes, without affecting the embryo quality or ploidy status. Usually, this so-called dual stimulation approach is characterized by a discontinuation of FSH administration for approximately 5 days between two consecutive stimulations. The role of dual uninterrupted ovarian stimulation has not yet been studied. Study design, size, duration: This was an open-label randomized controlled trial (RCT) with superiority design, performed in a single tertiary center. Power analysis indicated a required sample of 46 patients to detect superiority (defined as two surplus MII oocytes) of the dual stimulation group. Between October 2020 and September 2021, 70 patients were screened, 48 were randomized and 46 completed the study. Participants/materials, setting, methods: Women aged 25-40 with a serum anti-Müllerian hormone (AMH) level of ≤ 1.5 ng/mL, antral follicle count (AFC) of ≤ 6, or ≤ 5 oocytes after a previous stimulation, were eligible for inclusion. Randomization occurred only in case of ≤ 9 follicles of ≥ 11mm on the trigger day. In the control group, patients underwent one round of ovarian stimulation and oocyte retrieval only, while the study group had two uninterrupted rounds of ovarian stimulation and two retrievals. Main results and the role of chance: Baseline characteristics were similar between both groups. The cumulative number of COC and MII oocytes after completion of the second oocyte retrieval was similar in the control and study group [5.3 ± 2.7 versus 5.3 ± 3.1 [difference 95%CI (-1.7 to 1.7), p = 0.92] and 4.1 ± 2.5 versus 4.3 ± 2.7 [difference 95%CI (-1.7 to 1.3), p = 0.82]. Likewise, a comparable number of good quality embryos at day 3 was available (3.0 ± 2.0 versus 2.7 ± 2., p = 0.63). In the study group, the cancellation rate due to insufficient response to the second round of stimulation was 39.1%. When focusing on the first stimulation in both groups, there were no significant differences regarding basal FSH, FSH consumption and the number of preovulatory follicles. After the first oocyte retrieval, the mean number of COC and MII oocytes was significantly higher in the control group (who had human chorionic gonadotropin (hCG) triggering), compared to the study group (who had Gonadotropin Releasing Hormone (GnRH) agonist triggering) (5.3 ± 2.7 versus 3.3 ± 2.2, p = 0.004 and 4.2 ± 2.4 versus 2.9 ± 2.2, p = 0.05). Likewise, the number of good quality embryos on day 3 was significantly higher (3.0 ± 2.0 versus 1.9 ± 1.7, p = 0.04). Limitations, reasons for caution: This study was powered to demonstrate superiority for number of MII oocytes. Investigating the impact of dual stimulation on pregnancy rates would have required a larger sample size. Wider implications of the findings: The observed suboptimal oocyte yield after agonist triggering in poor responders is a reason for concern and further scrutiny, given that previous RCTs have shown similar outcomes in normal and high responders after hCG and GnRH agonist trigger. Trial registration number: NCT03846544